1978
DOI: 10.1128/jb.136.1.352-358.1978
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Oxidation of Methane and Methanol: Isolation of Methane-Utilizing Bacteria and Characterization of a Facultative Methane-Utilizing Isolate

Abstract: A methane-utilizing organism capable of growth both on methane and on more complex organic substrates as a sole source of carbon and energy, has been isolated and studied in detail. Suspensions of methane-grown cells of this organism oxidized C-1 compounds (methane, methanol, formaldehyde, formate); hydrocarbons (ethane, propane); primary alcohols (ethanol, propanol); primary aldehydes (acetaldehyde, propionaldehyde); alkenes (ethylene, propylene); dimethylether; and organic acids (acetate, malate, succinate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Other early studies reported the isolation of facultative methanotrophs from a rice paddy in South China, as well as from soils collected from an oil refinery in the Northeastern United States (Patel et al, 1978;Zhao & Hanson, 1984a, b). These strains were found to have the complete TCA cycle and two of them, strains R6 and 761H, were able to grow solely on glucose, but not with other sugars such as fructose, galactose, or sucrose.…”
Section: Initial Findings Of Facultative Methanotrophymentioning
confidence: 99%
“…Other early studies reported the isolation of facultative methanotrophs from a rice paddy in South China, as well as from soils collected from an oil refinery in the Northeastern United States (Patel et al, 1978;Zhao & Hanson, 1984a, b). These strains were found to have the complete TCA cycle and two of them, strains R6 and 761H, were able to grow solely on glucose, but not with other sugars such as fructose, galactose, or sucrose.…”
Section: Initial Findings Of Facultative Methanotrophymentioning
confidence: 99%
“…Although whole cells oxidized secondary butanol, the secondary alcohol dehydrogenase activity described by Hou et al (11) was not detected in either isolate. This unusual activity may therefore not be as widespread in methanotrophs as suggested by Hou and co-workers. In terms of presumptive classification, isolates H4-14 and 37W are similar to the other facultative methanotrophs M. organophilum XX (22, 23) and M. organophilum R6 (20) in that they have the ability to use both methane and more complex compounds as sole sources of carbon and energy. Before the work of Patt et al (22), this was not considered to be a feature of methanotrophs (28).…”
Section: Discussionmentioning
confidence: 89%
“…Since 1974, two facultative methanotrophs have been reported, both of which contained peripheral (type II) internal membrane systems and utilized the serine pathway for formaldehyde fixation (20,22). The isolation of these organisms has opened the way for detailed study of C-1 assimilation processes in methanotrophs (17)(18)(19).…”
mentioning
confidence: 99%
“…Cell-free extracts of methylotrophic bacteria and yeasts contained an oxidized nicotinamide adenine dinucleotidelinked secondary alcohol dehydrogenase (9, 22). Oxidation of straight-chain aldehydes in methylotrophic bacteria was catalyzed by an aldehyde dehydrogenase (11,19,20). The ability to oxidize n-alkanes was observed only with cells of the methylotrophic bacteria that had been grown on methane.…”
Section: Discussionmentioning
confidence: 99%
“…The methane-utilizing bacteria are geneiraly obligately dependent on methane or methanol as sole sources of carbon and energy for growth (1,5,7,12,25,28,32). Recently, there have been reports on the isolation and charac-720 terization of bacteria in pure culture that utilize methane as well as complex organic compounds as sources of carbon and energy (19,24,25).…”
mentioning
confidence: 99%